Вплив фінансових результатів на формування власного капіталу торгового підприємства - Джаббарова, С.Р.; Зубкова, В.І. (Культура народов Причерноморья, 2013)
У статті дано визначення поняттям «прибуток», «фінансові результати підприємства»,
«власний капітал». Розглянуто динаміку структури капіталу підприємств України за останні роки.
Проведено аналіз власного капіталу торговельного підприємства. Зроблена оцінка впливу факторів на
власний капітал торговельного підприємства з допомогою трехфакторной моделі Du Pont.
Представлені основні напрями підвищення прибутковості підприємств, а також заходи щодо
поліпшення ефективності використання власного капіталу підприємств.
Ключові слова: прибуток, збиток, фінансові результати, нерозподілений прибуток, чистий прибуток,
власний капітал. В статье дано определение понятиям «прибыль», «финансовые результаты предприятия»,
«собственный капитал». Рассмотрена динамика структуры капитала предприятий Украины за
последние года. Проведен анализ собственного капитала торгового предприятия. Произведена оценка
влияния факторов на собственный капитал торгового предприятия с помощью трехфакторной модели
Du Pont. Представлены основные направления повышения прибыльности предприятий, а также меры
по улучшению эффективности использования собственного капитала предприятий.
Ключевые слова: прибыль, убыток, финансовые результаты, нераспределенная прибыль, чистая
прибыль, собственный капитал. The article provides definitions of such notions as "profit", "financial results of enterprise", "equity".
Dynamics of capital pattern of Ukrainian enterprises by the main types of economic activities of late years has
been reviewed, which made it possible to estimate the share of equity of enterprises in aggregate of branches of
national economy of Ukraine, results have been analyzed and problems have been detected. The analysis of
commercial establishment equity has been performed and dependence of equity amount on business of enterprise
has been substantiated. The results of equity dynamics have been supplemented by the estimate of impact of
factors on the equity profitability by the instrumentality of a three-factor model Du Pont in the last two years.
The factors which detect effectiveness of enterprise running have been elicited. Their degree of impact on equity
has been estimated and tendencies in their changes and importance have been analyzed. The article suggests the
main methods to raise the profitability of enterprises own financial resources. The main ways to raise the
profitability of a commercial establishment have been performed, as well as the measures to improve the
profitability of using and distribution of the equity of the enterprise.
Keywords: profits, losses, equity, income, retained earnings and net income.